Implementation of Numeracy Action Board Media With Realistic Mathematic Education Approach to the Learning Outcomes of Grade 1 Elementary School Students - Nita, Cicilia Ika Rahayu; Haryanti, Julaita Putri; Ningsih, Puji Rahayu (Actual Insight, 2025)
The rapid development of society requires the field of education to continuously innovate in line with the evolving characteristics of contemporary students. Education must be implemented in accordance with the context of the times and the specific needs of learners. The low mathematics learning outcomes in addition and subtraction of numbers among Grade 1-A students at Kebonsari 2 State Elementary School in Malang present a challenge for teachers to design creative, contextual, and meaningful learning strategies. One such effort is the use of numeracy action board media integrated with the Realistic Mathematics Education approach, which is a mathematics learning method that connects abstract concepts with real-life situations familiar to students’ daily experiences, such as stories about shopping at small stalls or sharing cakes with friends. This study employed classroom action research based on the Hopkins model, which consists of two implementation cycles. The research subjects were 28 Grade 1-A students at Kebonsari 2 State Elementary School in Malang. The findings revealed an improvement in the percentage of students achieving mastery learning, from 46.62 percent in the pre-cycle to 79 percent in the first cycle, and a further significant increase to 93 percent in the second cycle. These results indicate that the use of numeracy action board media based on the Realistic Mathematics Education approach is effective in enhancing students’ mathematics learning outcomes. For future research, it is recommended to include statistical significance testing to strengthen the validity of the quantitative findings.